ALL-NEW X-MEN : ONE DOWN / VOLUME 5 - Bendis, Brian Michael; Immonen, Stuart; Grambadger, Wade Von (New York, NY: MARVEL WORLDWIDE, INC., 2015)
The Beast is tortured by his desicion to bring the original X-Men into the present, but can he repair the damage he's done while the future Brotherhood of Evil Mutant is still gunning for the time-tossed teens? The young X-Men will beed to rally to save themselves, but Jean Grey is...different. The Shi'ar trial has changed her. What does this mean for the future, for the past of the woman she's meant to become and for the rest of the X-Men? Timelines collide when the future Brotherhood exacts its final judgement on the All-New X-Men!
Contains material originally published in magazine form as All-new X-Men #25-30.
Keywords: X-Men (Fictitious characters) -- Comic books, strips, etc; Science fiction comic books, strips, etc; Superheroes -- Comic books, strips, etc; Graphic novels